Optimization of Paramecium caudatum Cultivation Condition Using Agricultural Wastes - Baiya, Songklod; Boonburapong, Bongkoj; Laloknam, Surasak (Burapha Science Journal, 2026)
This research aimed to optimize the agricultural waste culture medium and conditions of Paramecium caudatum. Agricultural wastes, sugarcane molasses (SGCM), soybean meal (SB), and rice straw (RS) were determined total reducing sugar and total protein contents. The results showed that SGCM contains the highest total reducing sugar content and following SB and RS. SB had the highest total protein content and following SGCM and RS. The impact of the agricultural waste culture medium on P. caudatum growth was conducted by varying concentrations of each agricultural wastes, 0.00, 0.01 0.10, 0.50, 1.00, 2.00, 5.00, and 10.00% (w/v). The optimal concentrations of each agricultural wastes are 0.1% (w/v) of SGCM, 1.0% (w/v) of SB, and 1.0% (w/v) of RS, respectively. The impact of the combination of agricultural wastes medium (0.1% (w/v) of SGCM, 1.0% (w/v) of SB, and 1.0% (w/v) of RS) on P. caudatum growth was investigated compared with each agricultural waste medium. The P. caudatum growth in a combination medium was significantly increased compared with a single medium. The effect of pH (pH 4-10) and temperature (10-40 °C) on P. caudatum growth were determined. The optimal cultivation condition of P. caudatum was cultivated in the combination of agricultural wastes medium with pH of 6.0 and temperature ranged between 25 and 30 °C. This finding indicated that this new modification agricultural wastes culture medium is suitable for P. caudatum growth used in ecotoxicological studies and animal feed production.